2016
DOI: 10.1097/aap.0000000000000386
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Comparison Between Intravenous and Perineural Dexamethasone for Ultrasound-Guided Infraclavicular Block

Abstract: Compared with its IV counterpart, PN dexamethasone (5 mg) provides a longer duration of motor block, sensory block, and postoperative analgesia for US-guided infraclavicular block. Future dose-finding studies are required to elucidate the optimal dose of dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 19 publications
1
77
0
Order By: Relevance
“…In a recent multicentre trial comparing intravenous (IV) and perineural (PN) administration of dexamethasone for ultrasound (US)-guided infraclavicular block (n = 150), we showed that the PN modality provided longer sensorimotor block and analgesia. 20 Nevertheless, other trials have failed to detect significant differences between IV and PN dexamethasone. 5,16,21,22 We speculated that these contradictory findings in the literature may stem from differences in the doses of dexamethasone and local anesthetic (LA) used as well as insufficient statistical power due to small sample sizes.…”
Section: Résumémentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent multicentre trial comparing intravenous (IV) and perineural (PN) administration of dexamethasone for ultrasound (US)-guided infraclavicular block (n = 150), we showed that the PN modality provided longer sensorimotor block and analgesia. 20 Nevertheless, other trials have failed to detect significant differences between IV and PN dexamethasone. 5,16,21,22 We speculated that these contradictory findings in the literature may stem from differences in the doses of dexamethasone and local anesthetic (LA) used as well as insufficient statistical power due to small sample sizes.…”
Section: Résumémentioning
confidence: 99%
“…Sensory block of the musculocutaneous, median, radial, and ulnar nerves was graded according to a three-point scale using a cold test: 0 = no block; 1 = analgesia (patient can feel touch but not cold sensation); 2 = anesthesia (patient cannot feel touch). 20,[24][25][26] The musculocutaneous, median, radial, and ulnar nerves were assessed on the lateral aspect of the forearm, the volar aspect of the thumb, the lateral aspect of the dorsum of the hand, and the volar aspect of the fifth finger, respectively. 20,[24][25][26] Motor block was also graded on a threepoint scale: 0 = no block; 1 = paresis; 2 = paralysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations